Diamond crystallization with a carbonyl nickel catalyst under high pressure and temperature. Issue 11 (23rd February 2016) - Liu, Xiaobing; Jia, Xiaopeng; Zhao, Ming; Ma, Hong-An
Abstract : In this work, we apply carbonyl nickel powders as a catalyst to grow diamond over a wide range of pressures and temperatures, and we report the first synthesis of high-quality diamonds containing nitrogen impurities with IaB characteristics. Abstract : For decades, the origin of aggregated nitrogen in diamond has been studied and has led to an important stage in solving the problems of natural diamond genesis. However, clarifying how B-centers (groups of four nitrogen atoms around a vacancy) form in diamond is still one of the most challenging issues in material science. In this work, we apply carbonyl nickel powders as a catalyst to grow diamond over a wide range of pressures, 5.0–6.2 GPa, and temperatures, 1300 to 1800 °C, and we report the first synthesis of high-quality diamonds containing nitrogen impurities with IaB characteristics. Both spontaneous nucleation of diamond and growth of diamond on seeds have been achieved by film growth and temperature gradient growth methods. By Fourier-transform infrared spectrometry, we reveal a novel formation mechanism for aggregated nitrogen impurities in B-centers, that is, B-centers can be readily aggregated by four C-centers (single-substitutional nitrogen atoms) during a diamond growth process under high pressure and temperature. High reaction temperatures can effectively contribute to the formation of nitrogen-vacancy defects in diamond and play a key role in the formation of B-centers during diamond growth. Our current findings will be helpful for further understanding and constructing a clear model of aggregated nitrogen, and thus provide us with deeper insights into the genesis of natural diamond.